IMPLEMENTASI KEBIJAKAN PENANGGULANGAN BANJIR PEMERINTAH KOTA MANADO (Studi Kasus di Kecamatan Singkil) - RAHAYU, INDAH PUTRI; ROMPAS, WELSON; DENGO, SALMIN (JURNAL ADMINISTRASI PUBLIK, 2021)
The purpose of this research is to find out how the flood management policies implemented by the ManadoCity Government in Singkil District. This research uses descriptive qualitative research using the Theory ofPolicy Implementation by Van Meter Van Horn. The data collection techniques used were observation,interview, and documentation. The data analysis technique used was data reduction, data presentation,conclusion and verification. The results of the study found that the flood management policies of theManado City Government in Singkil District had not been implemented thoroughly. This was found throughthe results of observations and interviews, namely that there are still some flood-prone areas in SingkilDistrict that have not been touched for the construction of embankments and river normalization as a formof flood control in Singkil District. It is hoped that there will be more attention from the Government in theconstruction of embankments and river normalization in Singkil District and awareness from thecommunity not to littering which is at risk of clogging drainage channels and causing flooding in ManadoCity.Keywords: Policy Implementation, Countermeasures, Flood